Analysis of strain rate sensitivity and strain rate hardening in Co–Cr–Ni–Mo wires drawn with different drawing practices - Gvk, Sai Srikanth (2021)
This study investigates the effect of strain rate (SR) on the strain rate sensitivity (SRS), strain rate work hardening (SRWH) in Co–35Ni–20Cr–10Mo alloy (MP35N) wires, subjected to drawing practices namely full die drawing (FDD) and half die drawing (HDD). The experimental results illustrate that the strength, and SRWH, of the drawn wires, increased with the rise of SR, whereas the SRS(m) and the ductility decreased with the increase of strain rate (10⁻⁶ s⁻¹ to 10⁻² s⁻¹). However, the relative strength, hardening, and the m values were observed to be higher in the FDD drawn wire when compared to the HDD drawn wire. The increase in strength and hardening rate of the FDD drawn wire with the rise in SR was ascribed to increased dislocation density and reduced twin thickness, and the increased SRS and ductility at low SR were attributed to the increased grain boundary (GB) activities. The HDD drawn wire had a relatively lower strength, SRWH and SRS rate at an SR of 10⁻⁶ s⁻¹ when compared to other SR, this was attributed to plastic flow localization, which led to the formation of shear bands in the material. An abnormal SRWH was observed in the HDD drawn wire tested to an SR of 10⁻² s⁻¹, where a Stage II hardening peak was observed at a very high strain, this was attributed to the solute segregation of the Mo atoms to the GB.